Analisis Tinjauan Pustaka Keterkaitan Stres Kerja, WorkLife Balance, dan Kinerja Karyawan di Era Hybrid Working - Syam, Selvira; Nurhidayah, Nurhidayah; Musdalifa, Musdalifa; Syam, Selvina; Idris, Hariany (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to analyze the relationship between job stress, work-life balance (WLB), and employee performance in the context of hybrid working. A descriptive qualitative approach with a literature review method was used, covering 20 publications from 2020 to 2025. The results show that job stress negatively affects employee performance by reducing motivation and productivity, while work-life balance plays an important role in reducing stress and improving performance. Hybrid working supports a better work-life balance when combined with effective communication, empathetic leadership, and technological support. Overall, maintaining a balance between flexibility and employee well-being is essential to enhance performance in the hybrid work era.